Modulation of Inter-kingdom Communication by PhcBSR Quorum Sensing System in Ralstonia solanacearum Phylotype I Strain GMI1000 - Li, Peng; Yin, Wenfang; Yan, Jinli; Chen, Yufan; Fu, Shuna; Song, Shihao; Zhou, Jianuan; Lyu, Mingfa; Deng, Yinyue; Zhang, Lian-Hui (Frontiers in Microbiology, 2017)
Ralstonia solanacearum is a ubiquitous soil-borne plant pathogenic bacterium, which frequently encounters and interacts with other soil cohabitants in competition for environmental niches. Ralsolamycin, which is encoded by the rmy genes, has been characterized as a novel inter-kingdom interaction signal that induces chlamydospore development in fungi. In this study, we provide the first genetic evidence that the rmy gene expression is controlled by the PhcBSR quorum sensing (QS) system in strain GMI1000. Mutation of phcB could lead to significant reduction of the expression levels of the genes involved in ralsolamycin biosynthesis. In addition, both the phcB and rmy mutants were attenuated in induction of chlamydospore formation in Fusarium oxysporum f. cubense and diminished in the ability to compete with the sugarcane pathogen Sporisorium scitamineum. Agreeable with the pattern of QS regulation, transcriptional expression analysis showed that the transcripts of the rmy genes were increased along with the increment of the bacterial population density. Taken together, the above findings provide new insights into the regulatory mechanisms that the QS system involves in governing the ralsolamycin inter-kingdom signaling system.